Preparing the groundwork for a Mindanao-Sulu historiography - Asain, Calbi A. (2008)
This paper attempts to identify possible approaches, methodologies, techniques, historical sources and materials useful in developing a historiography for Mindanao and Sulu. To be spelled out are approaches and methodologies best suited to the writing of the general history of Mindanao and Sulu as major historical arena in the country that local historians may find helpful.